KONDISI KECEMASAN PANITIA SEBELUM PENYELENGGARAAN EVENT COLOUR RUN NASMORI 2018 - SEPTAWAHYUNINGTYAS, IRDA; , PUDJIJUNIARTO (Jurnal Kesehatan Olahraga, 2019)
Abstract Coordination of event requires an experience. If it is the first time for organizing committee to coordinate such event, they will feel anxious because of several factors such as sponsors, pressure of job description from project leader, demand from participants, and success of the implementation day. The purpose of the research is to know the anxiety of committee before colour run event ?Nasmori? 2018. This research uses descriptive qualitative methode who uses open question (interview) which aims to describe the anxiety of committee before the event. This sampel of the experience is 12 committee of the colour run event ?NASMORI? 2018. The result of this study were 7 commite felt anxious and 5 committee not anxious. Committee anxiety is quite heavy, this factor is demands of participant, sponsors, deadline job description from the project leader and the success of colur run event ?Nasmori? 2018. But there are some committee don?t feel anxious because they have experience of organizing event and always positif thinking. Keyword : Anxiety, event management, psikology